การพัฒนาเทคนิคในการประเมินเวลาที่สารอยู่ในระบบโดยใช้เรดิโอนิวไคลด์เจเนอเรเตอร์ซีเซียม-137/แบเรียม-137m - ณัฏฐ์พัชร์ ภิรมย์กิจ (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
Characteristics of an industrial 137Cs/137mBa radionuclide generator was experimentally investigated in production of short lived 137mBa for radiotracer experiments such as in measurement of flow rate, determination of minimum mixing time and residence time distribution (RTD). The generator was produced by China Institute of Atomic Energy by absorption of 50 mCi (1.85 GBq) 137Cs onto KCoFC-SiO2 cation resin. 137mBa could be eluted by using 0.1M HCl with 0.9% NaCl solution. To allow 137mBa to build-up to its maximum activity, it was found that the next elution could be done after 6 minutes using 10 ml eluting solution at a flow rate of 20 ml/min. The experiment was then carried out in determining the RTD in a 157 L tank at varying flow rates i.e. 0.12, 0.24 and 0.83 L/s respectively. The detector system consisted of 4 sets of 2" x 2" NaI(Tl) detector connected to a LUDLUM 4612 12-channel counter and a microcomputer. The counter allowed up to 12 inputs and the outputs were displayed graphically on the microcomputer screen. The results were in good agreement with those obtained from the DTS PRO Software Package particularly after 50 s when the radiotracer was mixed thoroughly with water. The next experiment was carried out in a 21.2 L fluid mixer having 4 baffles using propellers and paddies at flow rates of 0.04 and 0.083 L/s respectively. The results were in good agreement with those obtained from those obtained from the software particularly after 100 s when the radiotracer was mixed thoroughly with water.